As dores de Maria reatualizadas na festa de Passos, em Pirenópolis – Goiás = The Maria's paints updated at the festa de Passos, in Pirenópolis - Goiás - Nascimento, Lucas Pedro do (Ciencias sociales y religión, 2017)
This work seeks to understand the reason why Catholics in a Goian municipality annually refurbish liturgical and ritualistically the pains of Mary in the Feast of Steps, and in the same proportion to understand their role in these popular religious manifestations. In order to do so, a participant observation survey of the religious event was conducted and an analysis of the data collected based on Eliade's discussion in The Sacred and the Profane (1992).